1984
DOI: 10.1007/bf00027296
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormone changes during storage root growth in Beta species

Abstract: The physiological and morphological factors necessary for efficient accumulation of sucrose in sugar beet (Beta vulgaris L.) are considered in relation to potential uses of plant growth regulators to modify the anatomy of storage roots so as to increase sucrose content and yield . The percentage of sucrose in root fresh and dry matter is closely related to root structure . Sugar beet, mangold and chard are three sub-species of Beta vulgaris that differ considerably in their anatomy, assimilate partitioning, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The rapid rate of sucrose accumulation after HI may be due to a higher cell division rate (Doney andTheurer, 1983, 1985) or to a different root development pattern for L19. Hosford et al (1984) found that three subspecies of Beta vulgaris differ consid erably in their seasonal development. Sugarbeet had continual cell division and expansion throughout the growing season, chard showed little or no cell expansion, while root growth in mangolds was essentially expansion of the parenchyma cells in the first 4 rings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The rapid rate of sucrose accumulation after HI may be due to a higher cell division rate (Doney andTheurer, 1983, 1985) or to a different root development pattern for L19. Hosford et al (1984) found that three subspecies of Beta vulgaris differ consid erably in their seasonal development. Sugarbeet had continual cell division and expansion throughout the growing season, chard showed little or no cell expansion, while root growth in mangolds was essentially expansion of the parenchyma cells in the first 4 rings.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, the controlling factors in L19 may be hormones or growth regulators that dictate when cell division and cell expansion occurs and the rate at which it proceeds, or they may be due to cell membrane transport kinetics. Hosford et al (1984), Saftner and Wyse (1984), and Saftner (1986) have observed that hormones or growth regulators can affect active sucrose uptake. Hosford et al (1984) observed that the concentrations of auxins and cytokinins found in roots during the growing season were different for mangold, chard, and sugarbeet.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Butterfass (1966) concluded that sugar beet plants with high endoreduplication have the lowest yield and suggested breeding tetraploid lines with low endopolyploidisation. On the other hand, there are different phytohormone levels in sugar beet genotypes that differ in root anatomy and sucrose concentration (Hasford et al. 1984).…”
Section: Discussionmentioning
confidence: 99%